Synthetic riboswitches for external regulation of genes transferred by replication-deficient and oncolytic adenoviruses - Ketzer, Patrick; Haas, Simon; Hartig, Jörg Steffen; Nettelbeck, Dirk M. (Nucleic acids research, 2012)
Abstract. Therapeutic gene transfer by replication-defective viral vectors or, for cancer treatment, by replication-competent oncolytic viruses shows high prom